Investigation of acoustic agglomeration efficiency using different working conditions of acoustic chamber - Kilikevičienė, Kristina; Chlebnikovas, Aleksandras (International Conference “Environmental Engineering”, 2023)
Particulate matter pollution is one of the main factors of atmospheric pollution. Due to its negative impact on both human health and the environment, it has become an actual problem in Lithuania and around the world. This paper will present a method for reducing the concentration of ultrafine particulate matter present in the atmosphere and causing pollution using different parameters of the acoustic chamber. Fine particles with an aerodynamic diameter of less than 2.5 μm are usually more saturated with toxic heavy metals and other pollutants due to their large surface area and strong surface activity. These particles go deep into the lungs and can cause lung cancer and other heart and lung diseases. Acoustic agglomeration is one of the most promising pretreatment technologies. Before using traditional particulate removal technologies, the ultrafine particles in the exhaust gas are exposed to a high-intensity sound wave, which promotes the relative motion of the aerosol particles and increases their agglomeration rate. Given results approved the high effect of reducing the amount of ultrafine particulate matter by agglomeration, thus, the reducing of the finest 0.3 μm particles is equal to more than half time at frequency of 34.75 kHz, 0.5 μm – more than half and more than three times at both frequencies of 20.06 kHz and 34.75 kHz respectively.